Do guidance and counseling teacher know about students mental health problems?: a qualitative study - Hartanto, Dody; Fauzia, Mufied; Azhari, Imam; Kusumaningtyas, Dian Artha; Rizal, Yenni (KONSELI: Jurnal Bimbingan dan Konseling (E-Journal), 2023)
It is known that adolescent mental health problems at school continue to increase in Indonesia. Guidance and counseling teachers are uniquely positioned to play a critical role in early identification and intervention. This research aims to determine teachers' understanding and knowledge regarding the forms of student mental health problems, efforts to deal with them and obstacles or problems in dealing with adolescent mental health problems at school as well as gaps or problems that schools have not been able to do to overcome mental health problems. The research method used in this research is qualitative. This research was conducted with a consensus qualitative study design. The research results show that teachers have recognized and understood the forms of mental health problems faced by students. The forms of mental health problems found through this research are anxiety, depression, severe emotional disorders, and attention deficit-hyperactivity disorder and have led to self-harm. Teachers are known to have used a variety of treatments aimed at promotion, prevention with class orientation, group and individual counseling. Problems that have not yet had to be addressed by schools are focused on the availability of infrastructure, collaboration and cooperation with parents or students' families as well as teacher capacity building programs. The results of this research contribute to guidance and counseling services in schools so that they can pay more attention to efforts to prevent and alleviate students' mental health problems.